2016
DOI: 10.1249/mss.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Do the Threshold Limit Values for Work in Hot Conditions Adequately Protect Workers?

Abstract: The current study demonstrated that heat balance was not achieved and ΔTb and ΔHb were inconsistent, suggesting that the TLV may not adequately protect workers during work in hot conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…While these guidelines certainly do not address the limits of heat exposure in other populations, recent work has suggested that they are inadequate in the average older adult (Lamarche et al 2017). In fact, they may even be insufficient to protect healthy active young adults (Meade et al 2015(Meade et al , 2016a(Meade et al , 2016b, which solidifies the unequivocal need for updated guidelines for all individuals. Specifically, that these new guidelines should be stratified based on susceptibility to heat-related illness or injury is paramount; however, the first critical step is to better define those who are at greatest risk.…”
Section: Introductionmentioning
confidence: 99%
“…While these guidelines certainly do not address the limits of heat exposure in other populations, recent work has suggested that they are inadequate in the average older adult (Lamarche et al 2017). In fact, they may even be insufficient to protect healthy active young adults (Meade et al 2015(Meade et al , 2016a(Meade et al , 2016b, which solidifies the unequivocal need for updated guidelines for all individuals. Specifically, that these new guidelines should be stratified based on susceptibility to heat-related illness or injury is paramount; however, the first critical step is to better define those who are at greatest risk.…”
Section: Introductionmentioning
confidence: 99%
“…Hailed as “one of the biggest mysteries in climate science” ( Tollefson, 2013), the slowdown of the Earth’s surface temperature warming in the period 1998–2013 undermined, for a number of years, the idea that human-generated greenhouse gases are the main driver and cause of climate change ( Nieves et al , 2015). During this period, the existing climate models were unable (on average) to reproduce the observed atmospheric temperature trend.…”
Section: Unaccounted Heat In Climate Researchmentioning
confidence: 99%
“…The ever-increasing decline in solar activity since 2000 was also considered as a possibility, since it reduces the amount of energy reaching the Earth ( Ineson et al , 2015). Ultimately, in 2015, Nieves and colleagues showed that what was interpreted as a change in the planet’s warming rate was, in fact, a redistribution of heat within the ocean ( Nieves et al , 2015). Specifically, Nieves et al , showed that heat moved from the surface of the Pacific Ocean to the deeper layers of the Western Pacific and Indian Oceans, a finding that was confirmed using a wealth of observational and simulated data.…”
Section: Unaccounted Heat In Climate Researchmentioning
confidence: 99%
See 2 more Smart Citations